Penguatan amaliah keshalihan mahasiswa melalui tutorial PAI di Universitas Pendidikan Indonesia: Pendekatan kokurikuler - Nurapipah, Iip; Anwar, Saepul; Firmansyah, Mokh Iman (Universitas Negeri Yogyakarta, 2025)
The reinforcement of Islamic Religious Education outside the classroom can utilize co-curricular activities to ensure the achievement of essential learning objectives, namely developing students' potential for faith, piety, and noble character. This study aims to analyze the role of tutorials in enhancing the religious practices of students at UPI, making this research important as it can provide solutions to address the shortage of classroom instructional hours. This research method is qualitative, with the subjects being the Head of the Tutorial Program, Lecturers, Tutors, and PAI participants. Data collection was conducted through interviews, observations, and documentation. Data analysis included reduction, presentation, verification, and conclusion drawing. The results of this study indicate that the reinforcement of religious practices is carried out through examples, encouragement, commands, practice, rewards, and the like. The material taught relates to the relationship with God (Habluminallah), the relationship with others (Habluminannas), and the relationship with the environment (Hablumin al-alam). The religious character formed strengthens individual religious commitment in worship or religious practice (the ritualistic dimension) and reinforces individual religious commitment in the dimension of effect or experience. This research implies the importance of responding to the limited classroom time for PAI in meeting the targeted PAI objectives through co-curricular programs to optimize these goals. Therefore, the researcher recommends efforts to enhance character formation or moral development through co-curricular activities in public schools and universities. Penguatan Pendidikan Agama Islam di luar kelas dapat menggunakan kegiatan kokurikuler guna memastikan tercapainya tujuan pembelajaran yang esensial yaitu mengembangkan potensi keimanan, ketakwaan, dan akhlak mulia mahasiswa. Penelitian ini bertujuan untuk menganalisis peran Tutorial dalam meningkatkan amaliah keshalihan mahasiswa di kampus UPI. Sehingga, penelitian ini penting karena dapat memberikan solusi untuk mengatasi kekurangan jam pelajaran di kelas. Metode penelitian ini adalah kualitatif dengan responden Ketua Penyelenggara Tutorial, Dosen, Tutor, dan peserta PAI. Pengumpulan data dilalukan melalui wawancara, observasi, dan dokumentasi. Analisis data meliputi reduksi, penyajian, verifikasi, dan penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa penguatan amaliah keshalihan dilakukan melalui teladan, anjuran, suruhan dan perintah, latihan, hadiah dan sejenisnya. Materi yang diajarkan adalah yang berkaitan dengan Habluminallah, Habluminannas, dan Hablumin al-alam. Kemudian, karakter religius yang dibentuk adalah menguatkan komitmen religius individu ke dalam peribadatan atau praktek agama (the ritualistic dimension) dan menguatkan komitmen religius individu ke dalam dimensi effect atau pengalaman.Penelitian ini berimplikasi pada pentingnya merespon keterbatasan waktu PAI di kelas dalam memenuhi kebutuhan beban yang ditargetkan oleh PAI melalui program kokurikuler untuk mengoptimalkan tujuan secara optimal. Sehingga, peneliti merekomendasikan dilaksanakannya upaya peningkatan pembentukan karakter atau pembentukan akhlak melalui kegiatan kokurikuler di sekolah-sekolah umum dan perguruan tinggi umum.